2004
DOI: 10.1002/app.13567
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mechanical properties of butyl methacrylate grafted wool fiber

Abstract: Because polymer-grafted wool fibers had been reported to have better functional performance, a K 2 S 2 O 8 -NaHSO 3 redox system was used as the initiator for the grafting copolymerization of butyl methacrylate (BMA) onto wool fibers. Grafted samples of wool-g-BMA with different grafting percentages (5.2-25.86) were obtained through variations in the monomer concentration in the reaction system. The evidence for grafting was provided by scanning electron microscopy and infrared spectroscopy. After the grafting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They observed that the moisture regain decreases, while the max load and strain at max load increase, with increasing grafting [141]. Similar systems were prepared by Meng [142] and Freddi et al [143], for the graft copolymerization of butyl methacrylate (BMA) and benzyl methacrylate (BzMA) onto wool fibres. They also observed that tensile strength increases with grafting, together with decreasing the elastic deformation for high modification degrees (>25% for BMA and >45% for BzMA) and decreasing the moisture retention and the molecular orientation (as seen by birefringence).…”
Section: Polyacrylates Polyacrylonitrile (Pan) and Polyacrylamide (Pam)mentioning
confidence: 76%
“…They observed that the moisture regain decreases, while the max load and strain at max load increase, with increasing grafting [141]. Similar systems were prepared by Meng [142] and Freddi et al [143], for the graft copolymerization of butyl methacrylate (BMA) and benzyl methacrylate (BzMA) onto wool fibres. They also observed that tensile strength increases with grafting, together with decreasing the elastic deformation for high modification degrees (>25% for BMA and >45% for BzMA) and decreasing the moisture retention and the molecular orientation (as seen by birefringence).…”
Section: Polyacrylates Polyacrylonitrile (Pan) and Polyacrylamide (Pam)mentioning
confidence: 76%